Pengaruh Model Pembelajaran Flipped Classroom Terhadap Hasil Belajar IPAS pada Kelas V di SDN 18 Balimbing - Salsabilah, Bahren; Zuliarni, Zuliarni; Eldani, Eldani; Hidayati, Abna (Indo-MathEdu Intellectuals Journal, 2024)
Based on observations of the learning process carried out at SDN 18 Balimbing, the learning process in science subjects is still teacher centred. In this case the teacher still explains the learning material from beginning to end, where students are not involved in the process of discussing the material. When the teacher is explaining the material, there is no student involvement in discussing the material, not all students pay attention and lack concentration in listening to the teacher's explanation and there are also students who carry out other activities that are not related to the current learning. This type of research is quantitative research using a Quasy Experiment approach. The population in this study was class V students at SDN 18 Balimbing. The samples for this research were class V.A as the experimental class and V.B as the control class, each consisting of 16 students. The data collection technique uses a test in the form of 40 objective questions, then the resulting data obtained is analyzed using the t-test. The results of this research show that the average score for the experimental class is 80.62, while the average score for the control class is 67.81. Based on the t-test calculation, the tcount ˃ ttable value is 3.364 ˃ 2.042, meaning there is a significant difference in learning outcome values ​​at the significance level ɑ 0.05. Thus, it can be concluded that the use of the Flipped Classroom learning model influences learning outcomes in class V science and science subjects at SDN 18 Balimbing